2015
DOI: 10.15288/jsad.2015.76.516
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-Induced Blackouts and Other Negative Outcomes During the Transition Out of College

Abstract: ABSTRACT. Objective:There is considerable debate about the prospective association between alcohol-dependence symptoms and alcohol-related blackouts. The goal of this study was to examine the associations among alcohol-dependence symptoms, blackouts, and social and emotional consequences during the transition out of college. Method: Participants (N = 829; 66% female) were part of a 6-year longitudinal study designed to explore alcohol use and risky behaviors during and after college. Data for these analyses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
34
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 40 publications
5
34
0
3
Order By: Relevance
“…A number of researchers have suggested that ‘blackout’ screening questions could be used to identify individuals at risk for alcohol-related consequences who, ostensibly, may benefit from intervention (Hingson, Zha, Simons-Morton, & White, 2016; Merrill et al, 2016; Mundt et al, 2012). Wilhite and Fromme (2015) took these recommendations a step further, suggesting that interventions emphasizing use of protective behavioral strategies may reduce alcohol problems among individuals with a history of alcohol-induced amnesia because use of these strategies may prevent rapid rise in BAC. However, studies to date have not examined whether drinkers with a history of alcohol-induced amnesia respond differently to intervention or the role that use of protective behavioral strategies and peak BAC may play in those outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…A number of researchers have suggested that ‘blackout’ screening questions could be used to identify individuals at risk for alcohol-related consequences who, ostensibly, may benefit from intervention (Hingson, Zha, Simons-Morton, & White, 2016; Merrill et al, 2016; Mundt et al, 2012). Wilhite and Fromme (2015) took these recommendations a step further, suggesting that interventions emphasizing use of protective behavioral strategies may reduce alcohol problems among individuals with a history of alcohol-induced amnesia because use of these strategies may prevent rapid rise in BAC. However, studies to date have not examined whether drinkers with a history of alcohol-induced amnesia respond differently to intervention or the role that use of protective behavioral strategies and peak BAC may play in those outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol consumption can produce problematic consequences including compromised work productivity (Rehm et al, 2009), distressing withdrawal symptoms (Hashimoto and Wiren, 2008), behavioral disinhibition and negative emotions (Hicks et al, 2012), and memory impairment and blackouts (Wilhite and Fromme, 2015). Drinking motives, or reasons for consuming alcohol, are important proximal determinants of the amount of alcohol consumed (Cox and Klinger, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Naert beslektet til hyppig beruselse, er å drikke så mye at man blir beruset i den grad at man får hukommelsestap ('black out') (White, 2003). Man tenkte tidligere at om man hadde episoder med 'black out', så var det en genetisk markør for utvikling av alkoholrelaterte problemer senere i livet, og dermed en saerlig viktig indikator (Wilhite & Fromme, 2015). Nyere studier har dog vist at mange ungdommer rapporterer 'black out'.…”
unclassified
“…Nyere studier har dog vist at mange ungdommer rapporterer 'black out'. Noen beregner forekomsten til å vaere over 50 prosent (Marino & Fromme, 2015;Schuckit et al, 2015;Wilhite & Fromme, 2015). Siden forekomsten av alkoholproblemer i befolkningen er langt fra så høy, innebaerer dette at de fleste av disse personene ikke vil utvikle alkoholproblemer senere i livet.…”
unclassified
See 1 more Smart Citation